Floripepiado: una propuesta de mobiliario a partir del entendimiento de la evolución del concepto de la casa (2020)
The project starts from a research about the evolution of domestic furniture in the West, where it seeks to understand how the different styles and furnishings that have existed throughout history have been transformed. This is because the furniture has been a great tool to understand the transformation that the house has had to this day. The spaces that make up the house are analyzed through history, as well as the evolution of the concepts that make up this space and that allow us to understand the house as a whole. Having understood the above, the project seeks to move towards the development of furniture for the house, using ornament as the main tool for its development. Therefore, it is explored how ornament has been used in the past in furniture and in the various spaces of the house.